Leading With Compassion - Dias Prasongko; Wigke Capri Arti (PCD Journal, 2021)
This article elaborates on two important elements of women's leadership. First, it explores how leadership theory has abandoned its masculine perspective in favour of a "more feminine" one. The COVID-19 pandemic, a crisis that crippled the socio-political structure, has contributed to this shift. Second, the experiences of grassroots leaders who are active in the domestic sphere have begun to be considered, as has their increased activeness in the public sphere during the COVID-19 pandemic. However, studies of women's leadership are highly elitist; such a paradigm is problematic, as it prioritises formal power structures and ignores the grassroots leaders who play a central role in maintaining the social order. This research finds that the pandemic has provided a valuable impetus not only for studies of formal elites but also women at the grassroots. Women have become highly powerful agents in the domestic sphere during the pandemic, and even expanded their agency into the public sphere. Women leaders have facilitated the implementation of government and community crisis response measures at the grassroots level.